AGE BASED PERPETRATION OF MENTAL STRESS USING PHARMED SOCIAL NETWORKING SITES ON INDIVIDUALS IN INDIA - Leelesh Sundaram.B; Asha Sundaram; V. Vishnu Priya; R. Gayathri (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The process of globalization in India has paved the way for rapid growth in social networking sites. The number of people using social networking sites has increased from time to time. The social networking sites have attracted people from different age groups. As a result of which it is used as a medium for illicit activity by criminals across the globe. Pharming is used as the most common way to commit a cyber crime through social networking sites. Pharming attacks divert users from real Web sites they are attempting to visit to false Websites. These false Web sites seem to be like genuine sites. The studies have enumerated that pharming has created adverse effects on the individuals, however the main concept that has to be noted is that social networking sites are used by people from different age groups. In this case a natural ambiguity arises as to whether as to who are likely to endure mental stress and become a victim of cyber crime through pharming in social networking sites. An empirical study done using non probability convenience sampling method and analysed using Chi square method reveals that there is no Association between mental Stress Perpetrated Through Cyber Crime By Pharmed Social Networking Sites on Individuals and age factor and the study recommends that the user have to spend more time to check the URL of the social networking sites.